Pengaruh Work Life Balance terhadap Kinerja Pegawai Sekretariat DPRD Kabupaten Deli Serdang - Nur Aulia Zannah; Fenty Zahara Nasution (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Work-life balance refers to a condition in which individuals are able to manage and allocate their time, energy, and attention proportionally between work demands and personal life. Performance is defined as the measurable outcomes achieved by individuals in carrying out their duties. This study aims to examine the effect of work-life balance on employee performance at the Secretariat of the Regional House of Representatives (DPRD) of Deli Serdang Regency. The proposed hypothesis states that there is a positive influence between work-life balance and employee performance. The study population consisted of 200 employees, and the sampling technique used was probability sampling, which provides equal opportunities for each member of the population to be selected. Based on the Yamane formula with a 10% error rate, a total of 67 respondents were obtained. Data were collected using a Likert-scale questionnaire, and the data were analyzed using a simple linear regression test. The results show a significance value of 0.000 < 0.05, indicating that the hypothesis is accepted. This means that work-life balance has a positive and significant effect on employee performance. The contribution of work-life balance to performance is 62.4%, while the remaining 37.6% is influenced by other factors.